BIOSTRATIGRAPHICAL IMPLICATIONS OF THE FOSSIL TUSKS’ STRUCTURE - Αθανασίου Α. (Bulletin of the Geological Society of Greece, 2006)
Fossil elephants of Eurasia are very useful for biostratigraphical correlations, as they were widespread geographically and they are generally common and well preserved as fossils. A relatively new method that contributes to the taxonomic identification of proboscidean tusks is the study of their microstructure, as it is expressed in their Schreger pattern. This pattern is characteristic of the proboscidean dentine. It is visible in tusk cross sections as intersecting spiral lines. The method can be applied in small, otherwise not determinable, tusk fragments to help with their taxonomic identification, making subsequently possible to come to biostratigraphical conclusions. The present study presents the application of this method in Greek samples, as well as the resulting taxonomic and biostratigraphic data